2022
DOI: 10.1002/jcsm.13145
|View full text |Cite
|
Sign up to set email alerts
|

Association between sarcopenia and oral functions in community‐dwelling older adults: A cross‐sectional study

Abstract: Background Few studies have examined the state of oral function in older adults with sarcopenia. We assessed the oral functions of community‐dwelling older adults with sarcopenia from multiple perspectives to clarify their potentially low oral function. Methods A total of 1517 (86.2%; 990 women, 527 men; mean age 76.1 ± 7.6 years) participants were included in this study. Grip strength, gait speed and skeletal muscle mass index were assessed, and sarcopenia was evaluated according to the criteria of the Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…In the present study, there were no statistically significant associations of the serum Cr/CysC ratio with occlusal force or masticatory function (Table 4), although a previous study has shown an association of sarcopenia with occlusal force and masticatory function 31 . However, in the current study, a lower number of remaining teeth was significantly correlated with low occlusal force and low masticatory function: OR, 0.48 (95% CI, 0.31–0.70) for low occlusal force, and 0.69 (95% CI, 0.48–0.96) for low masticatory function per five increments of teeth (Table 4).…”
Section: Discussioncontrasting
confidence: 83%
“…In the present study, there were no statistically significant associations of the serum Cr/CysC ratio with occlusal force or masticatory function (Table 4), although a previous study has shown an association of sarcopenia with occlusal force and masticatory function 31 . However, in the current study, a lower number of remaining teeth was significantly correlated with low occlusal force and low masticatory function: OR, 0.48 (95% CI, 0.31–0.70) for low occlusal force, and 0.69 (95% CI, 0.48–0.96) for low masticatory function per five increments of teeth (Table 4).…”
Section: Discussioncontrasting
confidence: 83%
“…Recently, Kugimiya et al reported that multiple aspects of oral functions including occlusal force, tongue-lip motor function, tongue pressure, masticatory function, and swallowing function were low among community-dwelling older adults with sarcopenia [ 50 ]. The group with a high OFI score and at high risk for oral frailty was found to have low grip strength, low muscle strength, and muscle mass, as reflected by the low values of cystatin C-related indices in the high-risk oral frailty group.…”
Section: Discussionmentioning
confidence: 99%
“…meat, fruit, and vegetables 31 , 32 . Thus, elderly subjects with impaired mastication are at higher risk of developing malnutrition and consequent sarcopenia due to low uptake of proteins and other essential nutrients 10 .…”
Section: Discussionmentioning
confidence: 99%